PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS V SD PADA MATA PELAJARAN MATEMATIKA - arkanjela girlani odang; siti indrawati kamba; rinaldi yusuf (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research is motivated by the low learning outcomes of Mathematics in class V of SD NEGERI CIMAHI 02. Caused by the learning process that is too monotonous. This study aims to improve student learning outcomes by using the Problem Based Learning Model. This study uses the Classroom Action Research Method (CAR) which is implemented in two cycles, where each cycle consists of the planning, action, observation, and reflection stages. The subjects of this study were students of class V of SD NEGERI CIMAHI 02, the number of students was 15 with 7 males and 8 females. Data collection was carried out through observation, tests and documentation. The results of the study showed a significant increase in student learning outcomes from only 13.33% from the pre-cycle to 80% in cycle II. Thus, the author concludes that the implementation of the Problem Based Learning Model was successful and effective in improving student learning outcomes.